Projecting the fiscal impact of immigration in the European Union. (17th December 2022) - Christl, Michael; Bélanger, Alain; Conte, Alessandra; Mazza, Jacopo; Narazani, Edlira
Abstract: The increasing flow of immigrants into Europe over the last decade has generated a range of considerations in the policy agenda of many receiving countries. One of the main considerations for policymakers and public opinion alike is whether immigrants contribute their 'fair' share to their host country's tax and welfare system. In this paper, we assess the net fiscal impact of intra‐EU and extra‐EU migration in 27 European Union (EU) Member States. We find that migrants in the EU, on average, contribute more than natives to welfare states. However, when we take an age‐specific life‐cycle perspective, we find that natives generally show a higher net fiscal contribution than both groups of migrants. Among migrants, extra‐EU migrants contribute less than intra‐EU migrants. We then use a demographic microsimulation model to project the potential net fiscal impact of migration in the EU into the future. We show that despite the fact that intra‐EU migration contributes to reduce the strong negative impact of population ageing, its contribution is not sufficient to offset the negative fiscal consequences.